The time course and chromosomal localization of recombination-related proteins at meiosis in the mouse are compatible with models that can resolve the early DNA-DNA interactions without reciprocal recombination. - Moens, P; Kolas, N; Tarsounas, M; Marcon, E; Cohen, P; Spyropoulos, B (2002)
During mouse meiosis, the early prophase RAD51/DMC1 recombination protein sites, which are associated with the chromosome cores and which serve as markers for ongoing DNA-DNA interactions, are in ten-fold excess of the eventual reciprocal recombinant events. Most, if not all, of these early interactions are eliminated as prophase progresses. The manner in which these sites are eliminated is the focus of this investigation. We report that these sites acquire replication protein A, RPA and the Escherichia coli MUTS homologue, MSH4p, and somewhat later the Bloom helicase, BLM, while simultaneously losing the RAD51/DMC1 component. Eventually the RPA component is also lost and BLM sites remain. At that time, the MUTL homologue, MLH1p, which is essential for reciprocal recombination in the mouse, appears in numbers and locations that correspond to the distribution of reciprocal recombination events. However, the MLH1 foci do not appear to coincide with the remaining BLM sites. The MLH1p is specifically localized to electron-microscope-defined recombination nodules. We consider the possibility that the homology-search RAD51/DMC1 complexes are involved in homologous chromosome synapsis but that most of these early DNA-DNA interactions are later resolved by the anti-recombination RPA/MSH4/BLM-topoisomerase complex, thereby preventing the formation of superfluous reciprocal recombinant events.